Accumulation and variation of rosmarinic acid content in Orthosiphon stamineus Benth. based on phenological stages - Truong, Do Minh; Bich Thu, Nguyen Thi; Nghi, Le Thanh (Academia Journal of Biology, 2012)
Orthosiphon Stamineus Benth. (Lamiaceae) is a medicinal herb trusted for many centuries for treating ailments of the kidney, bladder stone, urinary tract infection, liver and bladder problems, diabetes, rheumatism and gout. It is also used to reduce cholesterol and blood pressure. Rosmarinic acid is one of the most important and specific active compound in O. stamineus. The biological effects of rosmarinic acid have been proved. In the research, plant material was harvested at different phenological stages (before budding, full flowering, and after flowering) of the life cycle of the species. The content of rosmarinic acid in samples was measured using HPLC method. Results showed that the accumulation of rosmarinic acid in leaf was higher than that in other organs. The content of rosmarinic acid was increased gradually from before budding stage to flowering stage and reached the maximum content at time of after flowering stage. The content of rosmarinic acid of the 2nd variety was higher than that of the 1st variety at the same time (p < 0.05).